Influence of Sr2+ on Calcium‐Deficient Hydroxyapatite Formation Kinetics and Morphology in Partially Amorphized α‐TCP. Issue 3 (9th November 2015) - Hurle, Katrin; Neubauer, Juergen; Goetz‐Neunhoeffer, Friedlinde
Abstract : Hydration of partially amorphized α‐TCP powders with Sr 2+ concentrations ranging from 0 to 10 mol% substitution for Ca 2+ was analyzed by isothermal calorimetry and quantitative in‐situ XRD. Hydration of both crystalline α‐TCP and amorphous TCP (ATCP) forming CDHA was retarded to an increasing extent with increasing Sr 2+ content. Sr 2+ slightly reduced the crystallite size (XRD coherent scattering domains) of the CDHA formed during hydration, while the size of crystals visible under SEM was not noticeably affected. Reaction enthalpies of Δ H R(Sr‐α‐TCP→Sr‐CDHA) = 122 ± 8 J/gTCP and Δ H R(Sr‐ATCP→Sr‐CDHA) = 257 ± 8 J/gTCP were determined for the hydration of crystalline α‐TCP and ATCP containing 5 mol% Sr 2+ substitution for Ca 2+ . This is comparable with the corresponding reaction enthalpies previously obtained for undoped samples, which are 106 ± 7 J/gTCP for α‐TCP and 250 ± 7 J/gTCP for ATCP.